(untitled) (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2022)
This research is aimed at developing unique software to eliminate the problem when choosing one or another platform for the implementation of this kind of educational services. When developing software products, you never act on a whim - at least not unless you are planning business suicide. There is always a step-by-step plan that you follow to move from one stage to the next, making sure you don’t slip as you move from idea to implementation. This article is an immersive overview of the software development process. As part of the product discovery process, it’s all about connecting the dots between what you intend to build and whether or not someone will ever want you to use it. At this point, you should already know enough why you are creating a product and who its end users are. But you need a more coherent strategy to speed up the design process with your team. In addition to paid educational courses with documentary evidence of learning outcomes, there are also opportunities for free online education. Educational programs involve several levels of training, different in duration and quality.